2001
DOI: 10.1071/pp00129
|View full text |Cite
|
Sign up to set email alerts
|

Generation of selectable marker-free transgenic rice using double right-border (DRB) binary vectors

Abstract: Currently employed transformation systems require selectable marker genes encoding antibiotic or herbicide resistance, along with the gene of interest (GOI), to select transformed cells from among a large population of untransformed cells. The continued presence of these selectable markers, especially in food crops such as rice (Oryza sativa L.), is of increasing public concern. Techniques based on DNA recombination and Agrobacterium-mediated co-transformation with two binary vectors in a single or two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 21 publications
0
46
0
1
Order By: Relevance
“…Previously, we showed that such an approach is prone to underestimate transgenic locus number and therefore to present a distorted view of T-DNA linkage groups in plants (Vain et al 2003). Recently, it has been shown that 30-60% of the plants transformed with different T-DNAs can contain several types of T-DNA inserts (Lu et al 2001;Miller et al 2002) with some inserts containing either linked or unlinked T-DNAs or a mixture of both. The further development of the multiple T-DNA strategy relies, therefore, on a better understanding of locus constitution and T-DNA linkage in populations of transgenic plants.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previously, we showed that such an approach is prone to underestimate transgenic locus number and therefore to present a distorted view of T-DNA linkage groups in plants (Vain et al 2003). Recently, it has been shown that 30-60% of the plants transformed with different T-DNAs can contain several types of T-DNA inserts (Lu et al 2001;Miller et al 2002) with some inserts containing either linked or unlinked T-DNAs or a mixture of both. The further development of the multiple T-DNA strategy relies, therefore, on a better understanding of locus constitution and T-DNA linkage in populations of transgenic plants.…”
Section: Introductionmentioning
confidence: 96%
“…The multiple T-DNA approach was also the first to be implemented in cereals and is now used to produce markerfree transgenic rice Lu et al 2001), barley (Matthew et al 2001) and maize (Miller et al 2002) plants. Rice plants containing only a rice ragged stunt virus resistance transgene have been produced using the one vector/one strain version of this strategy (Lu et al 2001). The multiple T-DNA approach is likely to be one of the preferred type of "clean-gene" technology to produce transgenic cereal crops free of selectable marker genes in the near future.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A number of methods for marker gene removal from transgenic plants have been reported in the literature, including cotransformation of T-DNAs followed by segregation of the marker gene from the trait gene (Depicker et al 1985;de Frammond et al 1986;McKnight et al 1987;De Block and Debrouwer 1991;Komari et al 1996;De Neve et al 1997;Daley et al 1998;Xing et al 2000;Lu et al 2001;McCormac et al 2001), homologous recombination between direct repeats (Lichtenstein et al 1994;Zubko et al 2000) and sitespecific recombination. A number of site-specific recombinases of prokaryotic or yeast origin have been shown to function in transgenic plants for marker removal, including Cre/lox from bacteriophage P1 Ow 1990, phage Mu (Maeser andKahmann 1991).…”
Section: Introductionmentioning
confidence: 98%